Efektivitas Pelimpahan sebagian Kewenangan Bupati Kepada Kepala Distrik di Kabupaten Jayapura - Basri, Abdul Rahman; Silo, Akbar; Ohoiwutun, Yosephina; Muhdiarta, Untung (JURNAL EKOLOGI BIROKRASI, 2024)
Since the implementation of Law Number 23 of 2014 concerning Regional Government, Jayapura Regency has adopted a policy of delegating authority as an effort to improve the efficiency and effectiveness of government administration at the district level. This study aims to analyze the effectiveness of the delegation of authority from the Regent of Jayapura to the District Heads based on the Jayapura Regent Regulation Number 13 of 2019 on the Delegation of Partial Authority from the Regent to the District Heads to Perform Certain Local Government Affairs. This study uses a qualitative approach with data triangulation methods, including indepth interviews, observations, and document analysis. The results show that although there are some successes in the implementation of delegated authority, various obstacles remain, such as mismatches between the delegated authority and district capacities, lack of trained and competent human resources, and budget limitations. Additionally, the delegation process often lacks adequate accountability and transparency systems. The study also found that unclear policies and regulations, as well as complex bureaucratic processes, hinder the effectiveness of the delegated authority implementation. Some district heads feel that the delegated authority is insufficient to enable them to make quick and accurate decisions to serve local community interests. Recommendations from this study include improving human resource capacity at the district level, enhancing accountability and transparency systems, and simplifying bureaucratic processes to support the effectiveness of delegated authority. Thus, it is expected that the delegation of authority from the Regent of Jayapura to the District Heads can run more optimally and contribute positively to regional development and the improvement of public service quality